LEADERSHIP CHARACTERISTIC OF MALAYSIAN GIFTED AND TALENTED STUDENTS: IMPLICATION ON ISLAMIC YOUTH LEADERSHIP - Rorlinda Yusof, Mohd Sham Kamis, Salleh Huddin Abdul Rashid, Noorlin Maaulot, Md Jais Ismail (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Leadership is an important characteristic that allows Gifted and Talented (GT) students to assume responsibility shortly. This study aims to investigate the leadership characteristics’ levels and identify the component of leadership profiles amongst Malaysian GT students. A total of 171 students (93 from High School for Gifted Students and 78 from UKM Pre-University Programme) were involved in the study. The study employed a cross-sectional survey design, and data was collected using a questionnaire, namely Student Leadership Characteristics Questionnaire (SLCQ), and were analysed using SPSS version 19. Findings indicate that GT students possessed a high level of leadership characteristics. This study shows that collegiality received the highest score of leadership characteristics. Then, followed by leadership behaviour, influence efficiency, spiritual ethics, working relation, transformational, and cohesiveness.On the other hand, self-esteem, leadership efficacy, and visionary were among the average high, and self-monitoring was the lowest leadership characteristics. The findings also indicate that those female students possessed more top leadership characteristics in comparison to male students. Ethnicity such as Punjabi and Bumiputra Sabah and Sarawak natives possessed higher scores than the Chinese and Malays, whereas the Indians scored the lowest. Lastly, students from the High School Gifted Education Program possessed more top leadership characteristics than those from the Pre-University Gifted Program. This study has proven that leadership characteristics were embedded in the GT students’ personalities. The findings of this research provided a significant basis for the future leadership education program for the gifted students and the lead character development programs for Islamic youths in the school context.